Role of trpm8 Channels in Altered Cold Sensitivity of Corneal Primary Sensory Neurons Induced by Axonal Damage - Ugarte-Martinez, G; Madrid-Montecinos, R; Piña-Muñoz, R (Society for Neuroscience, 2019)
The cornea is extensively innervated by trigeminal ganglion cold thermoreceptor neurons expressing TRPM8 (transient receptor potetial cation channel subfamily M member 8). These neurons respond to cooling, hyperosmolarity and wetness of the corneal surface. Surgical injury of corneal nerve fibers alters tear production and often causes dry eye sensation. The contribution of TRPM8-expressing corneal cold-sensitive neurons (CCSNs) to these symptoms is unclear. Using extracellular recording of CCSNs nerve terminals combined with in vivo confocal tracking of reinnervation, Ca 2+imaging and patch-clamp recordings of fluorescent retrogradely labeled corneal neurons in culture, we analyzed the functional modifications of CCSNs induced by peripheral axonal damage in male mice. After injury, the percentage of CCSNs, the cold- A nd menthol-evoked intracellular [Ca 2+] rises and the TRPM8 current density in CCSNs were larger than in sham animals, with no differences in the brake K +current IKD. Active and passive membrane properties of CCSNs from both groups were alike and corresponded mainly to those of canonical low- A nd high-threshold cold thermoreceptor neurons. Ongoing firing activity and menthol sensitivity were higher in CCSNterminals of injured mice, an observation accounted for by mathematical modeling. These functional changes developed in parallel with a partial reinnervation of the cornea by TRPM8(+) fibers and with an increase in basal tearing in injured animals compared with sham mice. Our results unveil key TRPM8-dependent functional changes in CCSNs in response to injury, suggesting that increased tearing rate and ocular dryness sensation derived from deep surgical ablation of corneal nerves are due to enhanced functional expression of TRPM8 channels in these injured trigeminal primary sensory neurons. © 2019 Society for Neuroscience. All rights reserved.